The political economy of public sector reform and privatization - Suleiman, Ezra N., 1941-; Waterbury, John (Routledge, 2019)
This book suggests some of the ways in which levels of development shape public sector reform and privatization in developed and developing countries, showing that conservative as well as socialist governments were committed to increasing the state's guiding role in the political economy.